A systematic review on antibacterial activity of zinc against Streptococcus mutans - Manal Mohamed Almoudi; Alaa Sabah Hussein; Mohamed Ibrahim Abu Hassan; Nurhayati Mohamad Zain (Elsevier, 2018)
Objectives: The aim of this study was to systematically review the growth inhibition effectiveness of zinc against Streptococcus mutans. The main question was, "Does the zinc inhibit the growth of oral Streptococcus mutans in vitro? Methods: Literature search on PubMed, Medline, and science direct databases was carried out for in vitro studies published in English from 1990 to 2016, and the reported outcomes of minimum inhibitory concentration (MIC), minimum bactericidal concentrations (MBC), zone of inhibition (ZOI) and bacterial count method using colony forming unit (CFU) were used to assess the antibacterial effectiveness of zinc. Results: Seventeen studies were included in this review. Seven studies reported MIC and MBC. Four studies reported ZOI, and eight studies reported CFU. MIC values using zinc chloride and zinc oxide nanoparticles were ranged from 0.025 to 0.2 mM and 0.390 to 500 ± 306.18 µg/ml respectively. MBC values using zinc oxide nanoparticles have ranged from 3.125 to 500 µg/ml. ZOI ranged from no inhibition zone to 21 ± 1.4 mm using 23.1% zinc oxide. A considerable reduction in the bacterial count was reported after adding zinc. However, only two studies have reported no inhibitory effect of zinc. Conclusion: This review indicated a significant growth inhibition effectiveness of zinc even at lower concentrations which indicate it's safely to be used in oral health products. Keywords: Zinc, Antimicrobial, Antibacterial, Growth inhibition, S. mutans